جريمة اختلاس المال العام بين التشريع الإسلامي والقانوني الأردني - المناسية, محمد أمين محمد (جامعة الوادي university of eloued, 2021)
تناول البحث الاختلاس من عدة اعتبارات: اولا: أن له مفهومان، مفهوم عام وهوخطف المال الخاص والهروب به، وهو مفهوم المتقدمين من الفقهاء، ومفهوم معاصر عند الفقهاء المعاصرين وأصحاب القانون. ثانيا: تبين أن عقوبته تعزيرية فلا قطع فيها؛ لوجود شبهة دارئة للحد وهي نوع إهمال من صاحب المال في حفظه، وإمكان معرفة المختلس واللحوق به. ثالثا: كما إن هناك مفهوما خاصا وهو الاعتداء على الأموال العامة التي هي ملك للدولة، وهي أظهر الصور وأقربها إلى الذهن الآن، عند إطلاق كلمة" اختلاس"، وصورتها اعتداء موظف بالدولة على أموال هو مستأمن على حفظها. رابعا: أن التكييف الفقهي لجريمة الاختلاس يجعلها تدور بين جريمتي السرقة وخيانة الأمانة. وأن أقرب الصور لها في العصور المتقدمة هوالسرقة من بيت المال والغلول من الغنيمة. خامسا: اختلف الفقهاء في العقوبة المترتبة عليها، بعد اتفاقهم على أنها الكبائر. ودارت أقوالهم حول ثلاثة آراء(الاول): أنها جريمة تعدي على مال له فيه شبهة ملك فلا تعد سرقة، ومن ثم لا يقطع للشبهة، وهوقول الجمهور. (الثاني): أنها جريمة سرقة فيها القطع، وهذا رأي المالكية والظاهرية. أما (الثالث)، فكان للظاهرية وهو أنها جريمة سرقة بضابط معين وهوأن يكون للمختلس في المال المفروز نصيب. سادسا: سعت الشريعة في منع جريمة الاختلاس، بإيجاد وسائل للحفاظ على المال العام، كما تناولت الأسباب المفضية للاختلاس، والآثار المترتبة عليه. ووضع التدابير الوقائية للحيلولة دون وقوع أوانتشار جريمة الاختلاس على المال العام. الكلمات المفتاحية: الاختلاس؛ المال العام؛ السرقة؛ العقوبة؛ الاعتداء. Absrtact The research dealt with embezzlement from several considerations: First: It has two concepts، a general concept، which is the kidnapping of private money and escaping with it، and it is the concept of the forerunners of the jurists، and a contemporary concept according to contemporary jurists and legal scholars. Second: It was found that his punishment is punitive، and there is no interruption in it. Due to the existence of a suspicion that covers the limit، which is a type of neglect on the part of the owner of the money in preserving it، and the possibility of knowing the embezzler and being caught. Third: There is also a special concept، which is the attack on public funds that belong to the state، and it is the most obvious and closest to mind now، when the word “embezzlement” is used، and its image is an attack by a state employee on funds that he is entrusted with keeping. Fourth: The jurisprudential adaptation of the crime of embezzlement makes it revolve between the crimes of theft and breach of trust. And that the closest images to it in advanced ages are theft from the treasury and the looting of booty. Fifth: The jurists differed regarding her torment، after they agreed that it was a major sin. Their statements revolved around three statements (the first): It is a crime to infringe on money in which there is suspicion of its ownership، so it is not considered theft، and therefore it is not interrupted by suspicion، which is the opinion. from the audience. (Second): It is theft that includes pieces، and it is the doctrine of the Malikis. The third is for and the Zahiriyya ،which is that it is a crime of theft by an officer، and that the embezzler has a share in the screening. Sixth: Sharia worked to prevent the crime of embezzlement by finding means to preserve public money، and also addressed the causes and consequences of embezzlement. And put in place preventive measures to prevent the occurrence or spread of the crime of embezzlement of public money. Keywords: embezzlement; public money; theft; punishment; assaul
مقال
Keywords: الاختلاس؛ المال العام؛ السرقة؛ العقوبة؛ الاعتداء; embezzlement; public money; theft; punishment; assault